Anti-Inflammatory Effect of Centella asiatica (L.) Extract by Decreasing TNF-Î± Serum Levels in Rat Model of Traumatic Brain Injury - Nafiisah, Nafiisah; Faniyah, Falah; Pratama, Yoga Mulia (Majalah Kedokteran Bandung, 2021)
Centella asiatica (L.) has many active ingredients with many important roles, including as antioxidant, anti-inflamation and neuroprotectant. Centella asiatica (L.) can reduce inflammatory reactions by inhibiting the activity of TNF-Î±. Thus, Centella asiatica (L.) is a potential alternative therapy for traumatic brain injury by reducing inflammation via TNF-Î± expression modulation. This study aimed to determine the effect of Centella asiatica (L.) on serum TNF-Î± levels in rat model of traumatic brain injury. This study was conducted during the period of July 3-17, 2020 at the LPPT Unit IV, Gajah Mada University. This was a true experimental with post-test only control group study on 35 male wistar rats as the experimental animals. The rats were divided into 5 groups: P1, P2, and traumatic brain injury groups that received Centella asiatica (L.) treatement at 150, 300, and 600mg/kgBW/d doses, respectively. Blood samples were collected after the experimental animals were terminated to assess serum TNF-Î± levels. Mean TNF-Î± levels were 60,980±4,057, 76,931±0,698, P3=75,889±0,948, P4=75,868±1,163, and 74,508±1,126 for P1, P2, P3, P4, and P5, respectively. The Kruskal Wallis test results showed a statistically different between groups (p = 0.005). This study shows that Centella asiatica (L.) can decrease serum TNF-Î± level in rat model of traumatic brain injury.